Moderating effect of negative emotion differentiation in chronic stress and fatigue among Chinese employees - Lv, Wenhao; Qiu, Huake; Lu, Hongliang; Yajuan, Zhang; Yongjie, Ma; Xing, Chen; Zhu, Xia (Frontiers in Psychology, 2024)
According to the reactivity hypothesis and the diathesis-stress model, repeated activation of the stress system has a negative effect on health, and this effect may differ because of individual characteristics. Thus, the present study explores the effect of chronic stress on fatigue and investigates its mechanism. A questionnaire survey of 288 participants selected from the northwest part of China was conducted (13.89% females; ages ranged from 18 to 34 years, with M ± SD = 23.14 ± 3.79 years) on chronic stress, fatigue, depression, anxiety, and negative emotion differentiation. SPSS 28.0 was used to process descriptive statistics and correlation analysis and the PROCESS macro was used to analyze the moderated chained multi-mediation. Chronic stress was found to be positively correlated with fatigue, depression, and anxiety; depression and anxiety played a chained multi-mediating role between chronic stress and fatigue, and negative emotion differentiation played a moderating role in the chained multi-mediation model. Compared with depression, anxiety plays a more important role in the influence of chronic stress on fatigue.Therefore, it is necessary to pay more attention to anxiety symptoms and take appropriate intervention measures. Negative emotion differentiation plays a moderating role. Improving negative emotion differentiation through mindfulness and adaptive emotion regulation is an effective way to reduce the influence of chronic stress on fatigue.